BETWEEN FAITH AND FANDOM: HIJABI WOMEN ENGAGING WITH QUEER MANHWA IN DIGITAL MEDIA - Mulia, Yasmin; Safitri, Reza (Fakultas Ilmu Budaya, Universitas Brawijaya, 2026)
This study investigates how hijabi Muslim women’s engagement with queer manhwa is constructed, contested, and negotiated within contemporary social media discourse. The research examines public conversations across platform to explore how digital publics interpret the convergence of Islamic piety and participation in queer fandom cultures. Findings reveal a polarized discursive landscape in which hijabi readers are simultaneously policed for violating moral norms and defended as autonomous media consumers capable of complex interpretation. These debates illuminate how social media functions as a moral arena where notions of modesty, desire, cultural authenticity, and religious identity are actively negotiated. Rather than framing hijabi women’s engagement with queer manhwa as a contradiction, the discourses reveal dynamic processes of identity negotiation, boundary management, and affective participation shaped by both religious frameworks and digital affordances. This study contributes to broader discussions on gender, faith, digital fandom, and the changing face of Muslim womanhood in the era of globalized popular culture.